Analytical Study of Some Biomechanical Variables of 100m Runners and Their Relation with Iraqi League Achievement - Ameen, Mumtaz (Journal of Physical Education, 2023)
The research aimed at identifying the value of some biomechanical variables of 100m runners as well as identifying the relation of some biomechanical variables of 100m runners with achievement. The researchers used descriptive method on (5) runners of the Iraqi league for the season 2021 – 2022. They used two Sonny video cameras, photo finish for the finishing line, and 100m race according to IAAF rules. The researchers concluded that most biomechanical variable of 100m running were far from real values a matter that affected the subject’s achievement level. In addition to that, the average of stride frequency was within the perfect value.